2013
DOI: 10.1371/journal.ppat.1003451
|View full text |Cite
|
Sign up to set email alerts
|

miR-182 and miR-10a Are Key Regulators of Treg Specialisation and Stability during Schistosome and Leishmania-associated Inflammation

Abstract: A diverse suite of effector immune responses provide protection against various pathogens. However, the array of effector responses must be immunologically regulated to limit pathogen- and immune-associated damage. CD4+Foxp3+ regulatory T cells (Treg) calibrate immune responses; however, how Treg cells adapt to control different effector responses is unclear. To investigate the molecular mechanism of Treg diversity we used whole genome expression profiling and next generation small RNA sequencing of Treg cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 89 publications
(107 reference statements)
4
85
0
Order By: Relevance
“…During Leishmania-and Schistosome-associated inflammation, miR-182 and miR-10a have been found to be main regulators of the CD4 + Foxp3 + Tregs, and the IL-12/ IFN-γ axis regulates miR-10a as well as its putative transcription factor, Creb. TGF-β is involved in the stimulation of miR-10a expression during parasitic infection (Kelada et al 2013). Blocking the TGF-β pathway slows down the age-related thymic atrophy (Hauri-Hohl et al 2008).…”
Section: Role Of Microrna and Tgf-β Signaling Pathway In Parasitic Inmentioning
confidence: 99%
“…During Leishmania-and Schistosome-associated inflammation, miR-182 and miR-10a have been found to be main regulators of the CD4 + Foxp3 + Tregs, and the IL-12/ IFN-γ axis regulates miR-10a as well as its putative transcription factor, Creb. TGF-β is involved in the stimulation of miR-10a expression during parasitic infection (Kelada et al 2013). Blocking the TGF-β pathway slows down the age-related thymic atrophy (Hauri-Hohl et al 2008).…”
Section: Role Of Microrna and Tgf-β Signaling Pathway In Parasitic Inmentioning
confidence: 99%
“…Treg cells can be classified into two populations, naturally-occurring Treg (nTreg) cells that are generated in the thymus, and inducible Treg (iTreg) cells that arise from naïve CD4 + precursors in the periphery [90] . miRNAs play pivotal roles in the regulation of both Treg cell development and function [93,94] . miR10a is highly expressed in nTreg cells and can be induced by retinoic acid and TGFb in iTreg cells [90] .…”
Section: Mirnas and Regulatory T Cellsmentioning
confidence: 99%
“…MiR-182 was shown to be a key effector of the suppressor activity of regulatory T-cells during an immune response (30). It has been suggested that dysfunctional regulatory T-cells are associated with immune dysfunction in KD, but the mechanisms resulting in T-cell dysfunction remain unknown.…”
Section: Mir-182 and Immune Dysfunctionmentioning
confidence: 99%